Daclatasvir + sofosbuvir versus standard of care for hepatitis C genotype 3: a matching-adjusted indirect comparison. (March 2016) - Swallow, Elyse; Song, Jinlin; Yuan, Yong; Kalsekar, Anupama; Kelley, Caroline; Mu, Fan; Kim, Soomi; Noviello, Stephanie; Signorovitch, James
Aims: To compare the efficacy and tolerability of daclatasvir and sofosbuvir (DCV + SOF) versus SOF and ribavirin (SOF + R) and versus peginterferon-alfa plus ribavirin (A/R) in patients infected with hepatitis C genotype 3.Patients & methods: Clinical trials of SOF + R or A/R were identified in systematic literature reviews. The DCV+SOF population was adjusted via propensity score weighting to match average baseline characteristics to those reported for the comparator regimens.Results: The SVR12 rate was similar between DCV + SOF and SOF + R, and significantly higher with DCV + SOF than A/R. Rates of discontinuation due to AEs were similar or significantly lower in patients treated with DCV + SOF than SOF + R or A/R.Conclusion: With its high efficacy and improved tolerability, DCV + SOF is an important treatment for hepatitis C genotype 3.